A DNA Vaccine in Which the RSV-F Ectodomain Is Covalently Linked to the Burkholderia pseudomallei Antigens TssM and Hcp1 Augments the Humoral and Cytotoxic Response in Mice - Solodushko, Victor; Bitko, Vira; Barrington, Robert; Fouty, Brian (Frontiers in Immunology, 2019)
DNA vaccines have great potential to control infectious disease, particularly those caused by intracellular organisms. They are inexpensive to produce and can be quickly modified to combat emerging infectious threats, but often fail to generate a strong immunologic response limiting enthusiasm for their use in humans and animals. To improve the immunogenic response, we developed a DNA vaccine in which the F protein ectodomain of Respiratory Syncytial Virus (RSV-F) was covalently linked to specific antigens of interest. The presence of the RSV-F ectodomain allowed secretion of the translated fusion product out of the originally transfected cells followed by its active binding to adjacent cells. This allowed the targeting of a greater number of cells than those originally transfected, enhancing both humoral and cytotoxic immune responses against the expressed antigen(s). We developed an engrafted mouse model that used antigen-expressing tumor cells to assess the in vivo cytotoxic immune response to specific antigens. We then used this model to demonstrate that a DNA vaccine in which the RSV-F ectodomain is fused to two antigens expressed by Burkholderia pseudomallei, the intracellular gram-negative organism that causes melioidosis, generated a stronger cytotoxic response than a DNA vaccine that lacked the RSV-F sequence while still generating a robust humoral response.